The Tumble Inn - Loizeaux, William (Syracuse University Press, 2014)
"Tired of their high school teaching jobs and discouraged by their failed attempts at conceiving a child, Mark and Fran Finley decide they need a change in their lives. Abruptly, they leave their friends and family in suburban New Jersey to begin anew as innkeepers on a secluded lake in the Adirondack Mountains"--